2021
DOI: 10.3389/fcell.2021.651982
|View full text |Cite
|
Sign up to set email alerts
|

From Pinocytosis to Methuosis—Fluid Consumption as a Risk Factor for Cell Death

Abstract: The volumes of a cell [cell volume (CV)] and its organelles are adjusted by osmoregulatory processes. During pinocytosis, extracellular fluid volume equivalent to its CV is incorporated within an hour and membrane area equivalent to the cell’s surface within 30 min. Since neither fluid uptake nor membrane consumption leads to swelling or shrinkage, cells must be equipped with potent volume regulatory mechanisms. Normally, cells respond to outwardly or inwardly directed osmotic gradients by a volume decrease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 558 publications
(768 reference statements)
0
29
0
Order By: Relevance
“…While this pathway is also observed in diverse range of mammalian cells too, such as immune cells, endothelial and epithelial cells (Lin et al, 2020), they also play an essential role in cancer cells as reviewed in Ha et al (2016), Recouvreux and Commisso (2017), Commisso (2019), andRitter et al (2021). It has been identified that macropinocytosis is a mechanism by which cancer cells support their unique metabolic needs (Commisso et al, 2013), and has therefore increased the interest for anticancer therapies (Ritter et al, 2021;Song et al, 2021). The findings presented here open an interesting new aspect to macropinocytosis that suggests relevance to cancer cells too, as PIP3 domain dynamics are observed as self-organizing waves that are prone to be pinned and guided by strongly bended membranes, just as observed during the formation of macropinocytic cups (Veltman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this pathway is also observed in diverse range of mammalian cells too, such as immune cells, endothelial and epithelial cells (Lin et al, 2020), they also play an essential role in cancer cells as reviewed in Ha et al (2016), Recouvreux and Commisso (2017), Commisso (2019), andRitter et al (2021). It has been identified that macropinocytosis is a mechanism by which cancer cells support their unique metabolic needs (Commisso et al, 2013), and has therefore increased the interest for anticancer therapies (Ritter et al, 2021;Song et al, 2021). The findings presented here open an interesting new aspect to macropinocytosis that suggests relevance to cancer cells too, as PIP3 domain dynamics are observed as self-organizing waves that are prone to be pinned and guided by strongly bended membranes, just as observed during the formation of macropinocytic cups (Veltman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Following on that, another important aspect of PIP3 dynamics is the macropinocytosis (Buczynski et al, 1997 ; Hoeller et al, 2013 ; Veltman et al, 2016 ), which is a unique pathway of endocytosis to internalize large amounts of extracellular fluid, solutes and membrane (Lin et al, 2020 ). In non-mammalian cells, such as Dictyostelium cells, macropinocytosis requires PIP3 and the persistent activation of Ras Williams et al ( 2019 ) to form patches in macropinosomes Ritter et al ( 2021 ). While this pathway is also observed in diverse range of mammalian cells too, such as immune cells, endothelial and epithelial cells (Lin et al, 2020 ), they also play an essential role in cancer cells as reviewed in Ha et al ( 2016 ), Recouvreux and Commisso ( 2017 ), Zhang and Commisso ( 2019 ), and Ritter et al ( 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes in the cell occur against the background of minimal energy expenditure. Modern diagnosis of cell necrosis is based on the deteсе of lactate dehydrogenase activity and the use of specific cell-impermeamble DNA binding dyes (Rogers et al, 2017;Orning et al, 2017;Rijal et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, cell-free DNA and DNA neutrophils, the resulting protein complexes can be detected using PicoGreen ® and ELISA. Both morphology and cellrelated components of NETosis can be detected by flow cytometry (Zhelavskyi, 2015;Rijal et al, 2018).…”
Section: Immuno-reactive Cell Deathmentioning
confidence: 99%